Verrucous porokeratosis (porokeratosis ptychotropica) with dermal amyloid deposits - Yen-Fen Yu; Yu-Hung Wu (Wolters Kluwer Medknow Publications, 2013)
We report the case of a 43-year-old man with numerous pruritic verrucous papules and plaques on buttocks, natal cleft, penis, and scrotum for decades. He had already been diagnosed as having psoriasis or condyloma in different clinics, and received various topical medications and liquid nitrogen cryotherapy without improvement. On histopathology, there were several parakeratotic columns of cornoid lamella in the compact hyperkeratotic stratum corneum. The papillary dermis had amyloid deposition, which was positive for high molecular weight cytokeratin and congo red, indicating keratin-based amyloid. Interestingly, the cornoid lamella was negative for high molecular weight cytokeratin but showed weak positivity for cytokeratin 5/6.